Uluslararası inşaat sözleşmelerinde (FIDIC Kırmızı Kitap 1999’a göre) iş sahibinin ücret ödeme borcu - Kılıç, Mahmut Alper (My University, 2022)
Kırmızı Kitap, FIDIC tarafından düzenlenen, sözleşme modellerinden biridir. Bu sözleşme modeli, tasarımı iş sahibi tarafından hazırlanan projelerde kullanılmaktadır. Kırmızı Kitapta, inşaat sözleşmelerindeki tarafların, hak ve yükümlülükleri ayrıntılı olarak ele alınmıştır. Kırmızı Kitabın ekinde “Sözleşme Anlaşması”, “Sözleşmede Kullanılacak Formlar” ve “Ekler” tek tek hazırlanarak, sözleşmedeki tarafların istifadesine sunulmuştur. Ayrıca FIDIC Rehberi de yol gösterici olmaktadır. Bu sözleşme modelinde uyuşmazlık ve tahkim süreci de detaylı şekilde düzenlenmiştir. İş sahibinin ücret ödeme borcu; taraflar arasında, anlaşmazlığın en sık yaşandığı hususlardan biridir. Bu nedenle tezimizi bu konuda hazırlamayı tercih ettik. İş sahibinin ücret ödeme borcunu dört bölümde inceledik. Bu bölümler sırasıyla; ücretin belirlenmesi, ücretin ödenmesi, ücret ödeme borcuna aykırılığın sonuçları ve ücretin ödenmesine ilişkin ihtilaflarda uyuşmazlığın çözüm yollarıdır. Kırmızı Kitapta “sözleşmenin, teklif ekinde belirtilen ülkenin hukukuna tabi olduğu” belirtilmiştir. Türkiye’de hazırlanan sözleşmelerde Teklif Ekinde genellikle Türk Hukuku’na atıf yapıldığından tezimizde FIDIC ve Türk Hukukunu birçok noktada paralel inceledik. Yargıtay ve doktrinin ilgili konulardaki görüşlerine atıflar yaparak konuyu aydınlatmaya çalıştık.

The Red Book is one of the contract models regulated by FIDIC. This contract model is utilised in projects established by the employer. The rights and obligations of the parties for construction contracts are described in length in the Red Book. Contract Agreement, Forms to be used in the Contract, and Annexes have been developed one by one in the Red Book's annex and made available to the contract's parties. Furthermore, the FIDIC Manual serves as a guide for the parties. The dispute and arbitration processes are also detailed in this contract type. One of the most common disputes between the parties is the employer's obligation to pay the contract price. As a result, we felt compelled to write our thesis on this matter. We analyzed the employer's wage payment debt in four sections. These sections are as follows: the determination of the fee, the payment of the fee, the consequences of a breach of the fee payment debt, and the means of dispute settlement in fee payment issues. It is stated in the Red Book that “The Contract shall be governed by the law of the country stated in the Appendix to Tender. Considering Turkish Law is generally alluded to in the Appendix to Tender while drafting contracts in Turkey, we examined FIDIC and Turkish Law in a way that is parallel to each other in many aspects in our thesis. We attempted to shed light on the issue by referring to Supreme Court decisions and doctrine on relevant subjects.
Keywords: Arbitration; Civil Law; Contractor; Employer; Engineer; Fee; FIDIC; İş Sahibi; Kırmızı Kitap; Medeni hukuk; Mühendis; Red Book; Tahkim; Ücret; Yüklenici